INTEREST OF MICRO, SMALL AND MEDIUM ENTERPRISES (MSMES) IN CHOOSING BANKING FINANCING AND ITS IMPACT ON BUSINESS PERFORMANCE - Ikhsan Nendi; Koesharijadi Koesharijadi (Green Publisher, 2022)
This research aims to elaborate on the factors that make MSMEs choose an interest in choosing Islamic or conventional banking financing and measure how much interest MSMEs have in banking financing and then the good impact on the performance of MSMEs in the future after receiving financing from both Islamic and conventional banks. Finally, it is so that the difference between Islamic and conventional banking can be known in providing financing to MSMEs in Cirebon. The method used in this study is quantitative with primary data directly from MSMEs using questionnaire instruments distributed to 294 MSMEs in Cirebon consisting of types of industry, services and trade. Of the total samples taken, it was then divided into 2 (two) categories, namely Islamic and conventional banking, each of which was 50%. The analyst technique uses a differential test of 2 samples by going through a number of statistical tests. The results showed that the contribution of Micro, Small and Medium Enterprises (MSMEs) had a significant effect on increasing the amount of Indonesia's Gross Domestic Product (GDP), but MSMEs still left many problems to be able to grow better, one of which was due to financing (capital).